Cyclic [beta]-1,6 -1,3 Glucans Are Synthesized by Bradyrhizobium japonicum Bacteroids within Soybean (Glycine max) Root Nodules. - Gore, R. S. (1993)
We have previously reported that free-living cultures of Bradyrhizobium species produce novel oligosaccharides that are cyclic, contain between 10 and 13 glucose residues, and are linked by [beta]-1,6 and [beta]-1,3 glycosidic bonds (K.J. Miller, R.S. Gore, R. Johnson, A.J. Benesi, V.N. Reinhold [1990] J Bacteriol 172: 136-142). In the present study, we show that these glucans are also synthesized by bacteroids of Bradyrhizobium japonicum USDA 110 within Glycine max root nodules.